Comparison of Indonesian and English Segmental Phonemes - siregar, Durrah Mawwaddah; Siahaan , Rizky Putri Jasmine; Lubis , Yani (Jurnal Pendidikan Rafflesia, 2023)
communication that people use to express their feelings and thoughts to others. One linguistic subsystem is sound. In linguistics, these elements are often called phonemes. Phoneme is the smallest linguistic unit that can distinguish meaning. It should be understood that the sounds of the language are very important for the speaker to be able to understand what is being expressed or expressed by other speakers in the communication network. It is often difficult to understand the language of a speaker whose pronunciation is unclear. In fact, serious misunderstandings often occur due to unclear pronunciation. This study aims to (1) describe the characteristics of Indonesian segmental phonemes. (2) Describe the characteristics of segmental phonemes in Javanese. (3) Explain the difference between Indonesian and English segmental phoneme features. The results of the study show that there are six vowels in the Indonesian language, namely /i/, /u/, /e/, /ә/, /o/ and /a/. The Indonesian language has twenty-two, namely: /p/, /b/, /t/, /d/, /c/, /j/, /k/, /g/,/f/,/s/, /z / ,/š/, /x/,/h/, /m/,/n/, /ñ/, /ŋ/, /r/, /l/,/w/, /y/. English has vowels: /i:/, /i/, /e/, /ɛ/, /æ/, /a/, /u/, /ʊ/, /o/, /ͻ/, /ɒ/ , /ɨ/, /ᴈ/, /ә/ and /a/. Therefore, the results of this study show that the English language has fifteen vowel phonemes. English has twenty-four consonant phonemes: /p/, /b/, /t/, /d/, /k/ , /g/, /tʃ/, /ʤ/, /m/, /n /, /ŋ / , /l/, /f/, /v/, /θ/, /ð/, /s/, /z/, /r/, /ʃ/, /Ʒ/, /h/, /w/ and / j/. The data shows that there is a difference between Indonesian vowels and consonants and English vowels and consonants.communication that people use to express their feelings and thoughts to others. One linguistic subsystem is sound. In linguistics, these elements are often called phonemes. Phoneme is the smallest linguistic unit that can distinguish meaning. It should be understood that the sounds of the language are very important for the speaker to be able to understand what is being expressed or expressed by other speakers in the communication network. It is often difficult to understand the language of a speaker whose pronunciation is unclear. In fact, serious misunderstandings often occur due to unclear pronunciation. This study aims to (1) describe the characteristics of Indonesian segmental phonemes. (2) Describe the characteristics of segmental phonemes in Javanese. (3) Explain the difference between Indonesian and English segmental phoneme features. The results of the study show that there are six vowels in the Indonesian language, namely /i/, /u/, /e/, /ә/, /o/ and /a/. The Indonesian language has twenty-two, namely: /p/, /b/, /t/, /d/, /c/, /j/, /k/, /g/,/f/,/s/, /z / ,/š/, /x/,/h/, /m/,/n/, /ñ/, /ŋ/, /r/, /l/,/w/, /y/. English has vowels: /i:/, /i/, /e/, /ɛ/, /æ/, /a/, /u/, /ʊ/, /o/, /ͻ/, /ɒ/ , /ɨ/, /ᴈ/, /ә/ and /a/. Therefore, the results of this study show that the English language has fifteen vowel phonemes. English has twenty-four consonant phonemes: /p/, /b/, /t/, /d/, /k/ , /g/, /tʃ/, /ʤ/, /m/, /n /, /ŋ / , /l/, /f/, /v/, /θ/, /ð/, /s/, /z/, /r/, /ʃ/, /Ʒ/, /h/, /w/ and / j/. The data shows that there is a difference between Indonesian vowels and consonants and English vowels and consonants.